2020
DOI: 10.3390/app10051858
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trueness and Surface Microhardness on the Fitness of Ceramic Crowns

Abstract: This study aims to evaluate the fitness, surface microhardness, and trueness of crowns fabricated from three types of dental ceramic blocks (HASS Rosetta, IPS e.max CAD, and VITA Suprinity) and analyze the correlations between them. A crown was first designed in computer-aided design (CAD) software. To create a crown designed model (CDM), the design file was extracted from the CAD software, and a lithium disilicate block was processed from the file with a milling machine. To create a crown scanned model (CSM),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…There were some limitations to the present study. Previous studies have reported that the type of scanner can affect the marginal and internal fit of the prosthesis [43][44][45][46][47]. Depending on the results of the present in vitro study, there were few displacements of scanning in the desktop scanners, so further studies that consider the clinical environment are needed for the intraoral scanner.…”
Section: Discussionmentioning
confidence: 74%
“…There were some limitations to the present study. Previous studies have reported that the type of scanner can affect the marginal and internal fit of the prosthesis [43][44][45][46][47]. Depending on the results of the present in vitro study, there were few displacements of scanning in the desktop scanners, so further studies that consider the clinical environment are needed for the intraoral scanner.…”
Section: Discussionmentioning
confidence: 74%
“…The correlations were divided as per the size of the Pearson correlation coefficient (PCC), as reported previously [ 33 ]. The results of the correlation analysis among the variables were explained through the following criteria by the previous studies [ 14 , 16 , 33 ]: perfect (PCC = +1 or −1), strong (PCC = +0.7–+0.9 or −0.7–−0.9), moderate (PCC = +0.4–+0.6 or −0.4–−0.6), and weak (PCC = +0.1–+0.3 or −0.1–−0.3) (α = 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…An intraoral scanner is an essential tool in chairside computer-aided design and computer-aided manufacturing (CAD/CAM) system because it allows the acquisition of a virtual cast directly from the patient’s oral cavity without the need for any additional work process [ 11 , 12 , 13 , 14 , 15 ]. In the dental clinic, where quick fabrication is necessary, lithium disilicate ceramic material is preferred because it takes less milling time and less crystallization time [ 16 ]. The lithium disilicate ceramic crown is superior to a zirconia crown in terms of better aesthetics, faster fabrication, and easier post-processing process [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations